1991
DOI: 10.1123/jsep.13.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Enjoyment Scale: Two Validation Studies

Abstract: Two studies examined the reliability and validity of the Physical Activity Enjoyment Scale (PACES). In Study 1, each subject rode an exercise bicycle under control and external focus conditions. The PACES had high internal consistency in both conditions. As predicted, subjects reported enjoying the exercise more, as measured by the PACES, in the external focus condition. Moreover, there was a significant negative correlation in the control condition between subjects' PACES scores and their scores on a measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
685
1
23

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 984 publications
(757 citation statements)
references
References 0 publications
10
685
1
23
Order By: Relevance
“…In a study by Fridlung Dunton and Vaughan (2008), it was observed that when a participant anticipated positive emotional outcomes, such as enjoyment or being energized, they showed an increase in physical activity adoption and adherence. Additional research utilizing the Physical Activity Enjoyment Scale also addresses the concept of being energized by addressing the construct with an energizing/tiring dichotomy (Kendzierski and DeCarlo 1991). Taken together, the results of the present study suggest that the four most important factors of fun, satisfaction, commitment, and energize are intimately related and should be strongly considered when planning activities for older adults.…”
Section: Discussionmentioning
confidence: 55%
“…In a study by Fridlung Dunton and Vaughan (2008), it was observed that when a participant anticipated positive emotional outcomes, such as enjoyment or being energized, they showed an increase in physical activity adoption and adherence. Additional research utilizing the Physical Activity Enjoyment Scale also addresses the concept of being energized by addressing the construct with an energizing/tiring dichotomy (Kendzierski and DeCarlo 1991). Taken together, the results of the present study suggest that the four most important factors of fun, satisfaction, commitment, and energize are intimately related and should be strongly considered when planning activities for older adults.…”
Section: Discussionmentioning
confidence: 55%
“…Studies have demonstrated the reliability and validity of this measure. Specifically, the coefficient α is 0.96, and a testretest reliability of 0.60 was found for bicycling and 0.93 for jogging [45]. Additionally, enjoyment of physical activity has been significantly related to type of physical activity chosen by participants based on a Fisher's Exact Test (p=0.05 [45]).…”
Section: Physical Activity Enjoyment Scale (Paces [45])-mentioning
confidence: 96%
“…Enjoyment of the activity and intention to exercise were measured at the end of the fourth trial block. Enjoyment was measured using a short version (8-items) of the Physical Activity Enjoyment Scale (PAES; Kendzierski & DeCarlo, 1991).…”
Section: Self-efficacy Beliefs (Se)mentioning
confidence: 99%